R152a and R134a: High-Performance Working Fluids for Ejector Cooling Systems - Van Vu Nguyen; Yevgeniy Muralev (Journal of Technical Education Science, 2025)
This study presents a comprehensive thermodynamic analysis of an ejector cooling system (ECS) using a detailed one-dimensional mathematical model implemented in Engineering Equation Solver (EES) software. The research investigates the impact of key operational parameters such as secondary flow superheating, generator temperature, and primary nozzle superheat on system performance, specifically the entrainment ratio (ER) and coefficient of performance (COP). A comparative assessment of five working fluids (R134a, R152a, R600a, R1234ze(E), and R1233zd(E)) was conducted. Results indicate that secondary flow superheating generally enhances COP with minimal ER impact, while increased generator temperature improves both ER and COP. Primary nozzle superheat proved critical for overall performance. Among the investigated refrigerants, R134a and R152a demonstrated the highest COP. Notably, the low-GWP refrigerants R600a and R1234ze(E) showed promising and competitive performance, highlighting their potential as environmentally friendlier alternatives in heat-driven ejector cooling applications. The developed model serves as a robust tool for designing and analyzing ejector cooling systems.